Policy Formulation for The Establishment of Professional Certification Agency to Produce Competitive Graduates At Institute of Public Administration - ESKANDAR, ESKANDAR (Institut Pemerintahan Dalam Negeri, 2024)
The Institute of Public Administration (IPDN) is an Official Education Institution organizing the Vocational Education Program with the function of producing superior, professional, competitive, and integrity domestic government cadres. This institution faces a problem related to the policy formulation for the establishment of a Professional Certification Agency (LSP) to produce competitive graduates. This study aims to provide policy recommendations for the establishment of LSP to produce competitive graduates. This descriptive study used a qualitative approach. The data source was 30 respondents. Data collection techniques covered interviews, documentation studies, and literature studies. Data were analyzed in stages, namely data reduction, data presentation, and conclusions. The results of the analysis showed that the introduction and formulation of problems related to the lack of specific competencies possessed by IPDN Praja were carried out well; IPDN prioritized handling the problem related to the unavailability of LSP outside IPDN whose competency field specifications are in accordance with the study programs in IPDN and then set a strategy for the formation of the IPDN LSP; the establishment of an IPDN LSP did not face any serious obstacle; and the Rector of IPDN together with all Work Units within IPDN carried out the formulation and produced policies, namely the Rector's Decree Number: 500.10.2.2-225 of 2023 concerning the Establishment of the Professional Certification Agencies of the Institute of Public Administration. In this case, IPDN needs to prepare LSP establishment documents in accordance with BNSP Regulation Number 2/BNSP/III/2014 concerning the Establishment of LSP and LSP-P1 IPDN educational institutions. Besides conducting competency tests, it can also provide information about education and training as a prerequisite for participating in certification.